Islamic Communication Strategies for Environmental Sustainability in Local Traditions of Mandailing Natal, Indonesia - Matondang, Armansyah; Lahmuddin; Kholil, Syukur; Azahari, Helmi (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This article examines the Batang Pungkut river ban hole in Mandailing Natal district, an ethnic Mandailing tradition that contains local wisdom in managing the environment. The urgency of this phenomenon is researched because environmental problems are a common (global) problem and are seen as a threat to collective survival. The research question consists of four questions: how is the communication strategy of preservation, opening of the Lubuk Larangan, and communication barriers in preservation and opening, and what impact do residents feel due to the Lubuk Larangan? The research approach used is qualitative with a qualitative descriptive method. The theory used is Robert Cox's environmental communication strategy, with relevant supporting theories, and reviewed through the perspective of Islamic communication. The results concluded that the communication strategies used were persuasive, educative, and coercive. The communication strategy used refers to the value of local wisdom poda na lima (five wise advice), dalihan na tolu (kinship system), and the value of Islamic communication values, namely communicating clearly (qaulan matsuran) and in delivering messages in communication and being gentle (qaulan balighan). Lubuk larangan is managed in stages, starting from identification, planning, production, and evaluation, and is relevant to Robert Cox's environmental communication strategy. The obstacles faced are unlicensed mining, fish theft, environmentally unfriendly fishing gear, internal organizational dynamics, and community awareness. The novelty of the research lies in the presence of transcedental (divine) aspects in the communication strategy applied, and serves as a guideline to maintain their hope. The impacts residents feel are ecological, socio-cultural, economic, and religious. In addition to providing local impacts, this tradition simultaneously impacts the global community.